IDENTIFICATION OF INTERNAL AND EXTERNAL FACTORS OF VILLAGE-OWNED ENTERPRISES SUMBER SEJAHTERA AT PUJON KIDUL VILLAGE, MALANG REGENCY - Tifa Ervita Maharani; Riyanti Isaskar; Dina Novia Priminingtyas (Agricultural Socio-Economics Journal, 2023)
To strengthen the village economy, Village-Owned Enterprises (BUMDes) are commercial units owned and controlled by the government. To improve the local economy, BUMDes development activities have expanded in East Java. But there has been an outbreak of the COVID-19 virus that has hit the entire world, causing many negative aspects, including social, political, and economic life. One of the businesses affected by the economic downturn is the BUMDes. Aware of the internal and external environmental conditions of BUMDes became the target of research. 7S McKinsey's and PESTLE methods were used to facilitate the research. The 7S McKinsey approach is used to identify an organization's internal components, including strategy, system, structure, staff, style, skills, and shared values. PESTLE approach is used to determine how an organization affects the external economic environment, including political, economic, social, technological, legal, and environmental aspects. The results showed that the pandemic impacted business units in BUMDes. From the results of consumer tourism assessments, consumers or users of products or services most visitors feel that the tourism environment is very attractive, beautiful, clean, and comfortable, feel suitable to subscribe to products or services.